The heterogeneous effect of governance mechanisms on zero-leverage phenomenon across financial systems - Morais, F.; Serrasqueiro, Z.; Ramalho, J. J. S. (Corporate Governance, 2022)
Purpose: The purpose of this paper is to investigate whether the effect of country and corporate governance mechanisms on zero leverage is heterogeneous across market- and bank-based financial systems. Design/methodology/approach: Using logit regression methods and a sample of listed firms from 14 Western European countries for the 2002–2016 period, this study examines the propensity of firms having zero leverage in different financial systems. Findings: Country governance mechanisms have a heterogeneous effect on zero leverage, with higher quality mechanisms increasing zero-leverage propensity in bank-based countries and decreasing it in market-based countries. Board dimension and independency have no impact on zero leverage. A higher ownership concentration decreases the propensity for zero-leverage policies in bank-based countries. Research limitations/implications: This study’s findings show the importance of considering both country- and firm-level governance mechanisms when studying the zero-leverage phenomenon and that the effect of those mechanisms vary across financial and legal systems. Practical implications: For managers, this study suggests that stronger national governance makes difficult (favours) zero-leverage policies in market (bank)-based countries. In bank-based countries, it also suggests that the presence of shareholders that own a large stake makes the adoption of zero-leverage policies difficult. This last implication is also important for small shareholders by suggesting that investing in firms with a concentrated ownership reduces the risk that zero-leverage policies are adopted by entrenched reasons. Originality/value: To the best of the authors’ knowledge, this is the first study to consider simultaneously the effects of both country- and firm-level governance mechanisms on zero leverage and to allow such effects to vary across financial systems